Pharmacy for the soul : a comprehensive collection of meditations, relaxation and awareness exercises, and other practices for physical and emotional well-being - Osho. (b)
Pharmacy for the Soul suggests holistic remedies for a variety of ailments. Each section begins with a description and diagnosis of an emotional or physical ailment and then lists a number of prescriptions. Remedies include stretching techniques, meditations, laughter and breathing exercises, vocalizations, visualizations, chants, and massage, which are Osho's suggestions for helping to cure everything
Keywords: Self-help techniques; Conduct of life; Health